Assessment of Agreement of Wrist Bone Mineral Density with Spine and Hip Bone Mineral Density in Postmenopausal Women (Bangladesh Journal of Nuclear Medicine, 2019)
Objective: Worldwide, osteoporosis in postmenopausal women is a common public health problem. The measurement of bone mineral density (BMD) of spine and hip using central dual energy X-ray absorptiometry (DXA) is the most standard technique to diagnose osteoporosis. But in many circumstances, measurement of spine or hip BMD is quite difficult to carry out where wrist BMD can be used as an alternative. Moreover, wrist BMD can be done with smaller, cheaper, portable peripheral devices for screening osteoporosis at primary health care level. The objective of the study was to explore the agreement of wrist BMD with spine and hip BMD in postmenopausal women.Patients and Methods: This observational, cross sectional study was carried out at National Institute of Nuclear Medicine & Allied Sciences (NINMAS), Bangabandhu Sheikh Mujib Medical University (BSMMU) campus, from July 2017 to June 2018. A total of 110 postmenopausal women referred to NINMAS for BMD measurement were enrolled in this study after fulfilling selection criteria.  BMD of spine, right and left hip and wrist of enrolled subjects were measured by dual energy X-ray absorptiometry (DXA) scan by Stratos DR Bone densitometer.Results:  Agreement analysis done by kappa statistics revealed kappa value of 0.930 (p